2010
DOI: 10.1159/000322873
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Unintentional Injury in Older Adults

Abstract: Objective: To test the association between obesity and specific types and anatomical sites of unintentional injuries in older adults. Methods: Participants consisted of 52,857 men and women aged ≥65 years from the 2003 and 2005 Canadian Community Health Survey. Weight, height, and details on injuries occurring in the past year were obtained by survey. Results: Obese individuals had a higher risk for sprains/strains occurring at any anatomical site (odds ratio, 95% confidence interval: men 1.48, 1.48–1.62; wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Unintentional injuries such as sprains and strains occur more often [45] . Obesity is an important risk for frailty either through increased levels of inflammatory markers or through sarcopenia (OR 3.5 in 70-to 79-year-old females) [46] .…”
Section: Health Consequences Of Obesity In the Elderlymentioning
confidence: 99%
“…Unintentional injuries such as sprains and strains occur more often [45] . Obesity is an important risk for frailty either through increased levels of inflammatory markers or through sarcopenia (OR 3.5 in 70-to 79-year-old females) [46] .…”
Section: Health Consequences Of Obesity In the Elderlymentioning
confidence: 99%
“…Observational data show that unintentional weight loss is associated with increased disability [78, 79]. In addition, overweight and mild obesity are associated with protection against osteoporosis and fractures [80], with better prognostic recovery from certain illness and injuries [81], and with reduced mortality risk [81] in older adults. A position statement from The Obesity Society states that “ appropriate treatment for obesity in older persons is controversial because of the reduction in relative health risks associated with increasing BMI and the concern that weight loss could have potential harmful effects ” [37].…”
Section: Risks Of Obesity Treatment In Older Adultsmentioning
confidence: 99%
“…Studies conducted among hospital workers (Kouvonen et al, 2013) and manufacturing workers (Pollack et al, 2007) reported a significant association between fracture and obesity. Bouchard, Pickett, and Janssen (2010) revealed that excessive fat would protect the risk of fracture in older adults when falling because of greater cushioning. However, our study found obese workers had a significant excess risk of fracture and falling.…”
Section: Discussionmentioning
confidence: 99%